Genome-Wide Expression Analysis of Glyoxalase I Genes Under Hyperosmotic Stress and Existence of a Stress-Responsive Mitochondrial Glyoxalase I Activity in Durum Wheat (Triticum durum Desf.) - Soccio, Mario; Marangi, Marianna; Laus, Maura N. (Frontiers in Plant Science, 2022)
Glyoxalase I (GLYI) catalyses the rate-limiting step of the glyoxalase pathway that, in the presence of GSH, detoxifies the cytotoxic molecule methylglyoxal (MG) into the non-toxic D-lactate. In plants, MG levels rise under various abiotic stresses, so GLYI may play a crucial role in providing stress tolerance. In this study, a comprehensive genome database analysis was performed in durum wheat (Triticum durum Desf.), identifying 27 candidate GLYI genes (TdGLYI). However, further analyses of phylogenetic relationships and conserved GLYI binding sites indicated that only nine genes encode for putative functionally active TdGLYI enzymes, whose distribution was predicted in three different subcellular compartments, namely cytoplasm, plastids and mitochondria. Expression profile by qRT-PCR analysis revealed that most of the putative active TdGLYI genes were up-regulated by salt and osmotic stress in roots and shoots from 4-day-old seedlings, although a different behaviour was observed between the two types of stress and tissue. Accordingly, in the same tissues, hyperosmotic stress induced an increase (up to about 40%) of both GLYI activity and MG content as well as a decrease of GSH (up to about -60%) and an increase of GSSG content (up to about 7-fold) with a consequent strong decrease of the GSH/GSSG ratio (up to about -95%). Interestingly, in this study, we reported the first demonstration of the existence of GLYI activity in highly purified mitochondrial fraction. In particular, GLYI activity was measured in mitochondria from durum wheat (DWM), showing hyperbolic kinetics with Km and Vmax values equal to 92 ± 0.2 µM and 0.519 ± 0.004 µmol min-1  mg-1 of proteins, respectively. DWM-GLYI resulted inhibited in a competitive manner by GSH (Ki = 6.5 ± 0.7 mM), activated by Zn2+ and increased, up to about 35% and 55%, under salt and osmotic stress, respectively. In the whole, this study provides basis about the physiological significance of GLYI in durum wheat, by highlighting the role of this enzyme in the early response of seedlings to hyperosmotic stress. Finally, our results strongly suggest the existence of a complete mitochondrial glyoxalase pathway in durum wheat actively involved in MG detoxification under hyperosmotic stress.